Single-cell RNA sequencing reveals heterogeneity among AT2 epithelial cells in the lung adenocarcinoma microenvironment - Cao, Zimeng; Bai, Xuefeng; Li, Jing; Cai, Jinru; Cao, Gang; Xiao, Yuncai; Zhou, Wei (Frontiers in Immunology, 2025)
IntroductionLung cancer is a highly heterogeneous disease, and the tumor microenvironment (TME) characteristics are closely related to disease progression and treatment outcomes. We elucidated the cell type-specific transcriptome landscape of cancer cells and the effect of the TME on lung adenocarcinoma (LUAD).MethodsSingle-cell RNA sequencing of the LUAD tissues and matched adjacent normal tissues of three patients in the early-stage via histopathological and immunohistochemical confirmation.ResultsThe results revealed the landscape of 68,579 cells in LUAD microenvironment, and highly heterogeneous AT2 cells are crucial source of lung epithelial cell carcinogenesis. Genes KRT81, SPP1, PCDH7, SLC2A1, and TET1 were significantly upregulated in tumor tissues and associated with poor prognosis and survival, providing insights for exploring lung cancer biomarkers in future studies. Trajectory analysis identified ERBB4, SEMA4A, GCNT2 and SOX4 as key factors in AT2 cells that may promote cell proliferation, migration, or epithelial-mesenchymal transition (EMT) during the progression of lung adenocarcinoma (LUAD). We elucidated the transcription factor–target gene regulatory network involving NKX2-1 and TEAD1 in malignant tumor cells derived from AT2 cells. The findings indicated that malignant AT2 cells regulate communication between epithelial and immune cells in the TME by predicted FN1-CD44 and CADM1-CADM1 ligand-receptor interactions, which ultimately suppresses the host immune response.DiscussionThis comprehensive single-cell analysis increases our understanding of AT2 cells molecular and dynamics of metastatic lung cancer. In summary, single-cell RNA profiling of LUAD offers valuable prognostic insights based on AT2 cell types and identifies potential biomarkers for therapeutic responses, aiding the future development of LUAD treatment strategies.